Use of an Electronic Medical Record to Create the Marshfield Clinic Twin/Multiple Birth Cohort. Issue 8 (22nd September 2014) - Mayer, John; Kitchner, Terrie; Ye, Zhan; Zhou, Zhiyi; He, Min; Schrodi, Steven J.; Hebbring, Scott J.
ABSTRACT Population‐based genetic analyses, such as the Genome‐Wide Association Study (GWAS), have proven powerful for describing the genetic complexities of common disease in epidemiologic research. However, the significant challenges faced by population‐based study designs have resulted in revitalization of family‐based approaches, including twin studies. Twin studies are unique in their ability to ascertain both heritable and environmental contributions to human disease. Several regional and national twin registries have been constructed using a variety of methods to identify potential twins. A significant challenge in constructing these large twin registries includes the substantial resources required to recruit participants, collect phenotypic data, and update the registries as time progresses. Here we describe the use of the Marshfield Clinic electronic medical record (EMR) to identify a cohort of 19, 226 patients enriched for twins or multiples. This cohort defines the Marshfield Clinic Twin/Multiple Birth Cohort (MCTC). An EMR system provides both a mechanism to identify potential twins and a source of detailed phenotypic data in near real time without the need for patient contact outside standard medical care. To demonstrate that the MCTC can be used for genetic‐based epidemiologic research, concordance rates for muscular dystrophy (MD) and fragile‐X syndrome—two highly heritable diseases—were assessed. Observations indicate that both MD and fragile‐X syndrome are highly correlated among affected twins in the MCTC (P ≅ 3.7 × 10−6 and 1.1 × 10−4, respectively). These findings suggest that EMR systems may not only be an effective resource for predicting families of twins, but can also be rapidly applied to epidemiologic research.